Antibacterial and antibiofilm activity of the cell-free supernatant of lactic acid bacteria from burong mustasa against streptococcus mutans - Amistoso, Marmee Mathea
Dental caries, a non-communicable disease, is a major global health problem mainly caused by Streptococcus mutans. The pathogen of interest is known to infect the oral cavity through biofilm formation. For the mitigation of the pathogen, this study focused on burong mustasa, which is a Philippine fermented food that has been investigated for the presence of microorganisms. Lactic acid bacteria (LAB) were studied to be present in this fermented food. Furthermore, the cell-free supernatants (CFS) of certain species of lactic acid bacteria are known to fight off other bacteria. Hence, the aim of this study was to determine the antibacterial and antibiofilm activity of cell-free supernatants, which will be extracted from broth cultures of lactic acid bacteria isolated from burong mustasa, against Streptococcus mutans. Seven isolated lactic acid bacterial colonies showed antibacterial activity against S. mutans. Based on the zones of inhibition exhibited, five out of the seven colonies had their cell-free supernatants extracted. The antibacterial activity of two colonies were observed upon increasing the volume used. The antibiofilm activity results, however, were inconclusive since biofilm formation could not be confirmed.